The Influence of Hr Information Systems, Competence, and Work Discipline on Work Productivity Post-Merger Bank Syariah Indonesia: (Branch Mataram Pajenggik 1) - Septianingsih, Harum; Saibil, Defi Insani (UIN Sunan Kalijaga Yogyakarta, 2023)
Research Aims: HR information systems, competencies, and work discipline are the independent variables while work productivity is the dependent variable used. Methodology: The case studies that became the research population were employees of Bank Syariah Indonesia Mataram Pejanggik 1 Branch Office. This research is a quantitative research with saturated sampling technique used in determining the sample. The distribution of respondents obtained was 40 filled out questionnaires. Data analysis method with IBM SPSS 26 because it uses multiple linear regression analysis. Research Findings: The results of this study were obtained simultaneously from the three variables influencing employee work productivity. Meanwhile, if partially obtained the results of information system variables, and work discipline have a positive and significant effect on work productivity. But the competency variable partially has no positive and significant effect on employee work productivity. The results of this study are that Bank Syariah Indonesia Pejanggik 1 Branch has implemented an HR information system that is accurate and clear, as well as good work discipline, even though there are still employees who are not competent in their fields.